12 epic polar adventures - Ventura, Marne (Epic adventures., 2019)
Highlights twelve polar adventures around the world including visiting the Falkland Islands, the Wendell Sea, and the North Pole. Contains a world map, color photographs, statistics, a glossary, and resources for further reading.